Factors Influencing Risky Sexual Behaviors among Nursing Students in a Thai Public University, Southern Thailand - Pichaisongkram, Sirakhrin; Doloh, Muhammadfitree; Dulasa, Shamiyatulhuda; Cheni, Bismee; Madaehae, Surida; Daoh, Nureeya; Buesa, Badree; Hayeeyakareeya, Amanee; Kaewsalam, Aree; chewae, Halisna (Princess of Naradhiwas University Journal, 2025)
Background and objectives Risky sexual behaviors among adolescents and young adults remain a major public health concern in Thailand, leading to unintended pregnancies, sexually transmitted infections, and psychosocial consequences. Nursing students, who are in late adolescence to early adulthood, are particularly vulnerable while also being future health professionals expected to serve as role models for healthy behaviors. This study aims to examine the factors influencing risky sexual behaviors among nursing students in a Thai Public University, Southern Thailand. Methods This was a descriptive study designed to identify predictive factors. The samples were 143 nursing students in years 1-4. The instruments consist of the 4 questionnaires assessing: demographic questionnaires, risk behavior related to substance use questionnaires, sexual risk behaviors questionnaires, and stress assessment questionnaires. Content validity was evaluated by three experts, yielding an Index of Item-Objective Congruence (IOC) were 0.75-0.98. Reliability testing revealed Cronbach’s alpha coefficients of 0.75 and 0.85 for the risk of substance use and stress assessment questionnaires, respectively, and KR-20 of 0.84 for the sexual risk behavior questionnaire. Data were analyzed using descriptive statistics, Pearson Correlation Coefficient, and Enter Regression Analysis. Results The findings indicated that significant factor influencing sexual risk behaviors among nursing students was risk behaviors related to substance use (B = .27, β=.28, t = 4.31). This factor was found to be a statistically significant predictor, collectively explaining 11 % of the variance in sexual risk behaviors (R² = .11, F =9.29) Conclusions and Recommendations The research highlights the factor influencing risky sexual behaviors is risky behavior related to substance use. This is a crucial element for future consideration when planning interventions to prevent and address risky sexual behaviors among nursing students.